Games of No Chance 3 2009
DOI: 10.1017/cbo9780511807251.002
|View full text |Cite
|
Sign up to set email alerts
|

Playing games with algorithms: Algorithmic combinatorial game theory

Abstract: Combinatorial games lead to several interesting, clean problems in algorithms and complexity theory, many of which remain open. The purpose of this paper is to provide an overview of the area to encourage further research. In particular, we begin with general background in Combinatorial Game Theory, which analyzes ideal play in perfect-information games, and Constraint Logic, which provides a framework for showing hardness. Then we survey results about the complexity of determining ideal play in these games, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 75 publications
0
30
0
Order By: Relevance
“…They have a long history. Hearn [36] and Demaine et al [18] showed that tiles can be arranged to create logic gates and used this technique to prove pspace-completeness for a variety of sliding-block puzzles. Hearn expressed the idea of building computers from the sliding blocks-many of the logic gates could be connected together, and the user could propagate a signal from one gate to the next by sliding intermediate tiles.…”
Section: Underactuated Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a long history. Hearn [36] and Demaine et al [18] showed that tiles can be arranged to create logic gates and used this technique to prove pspace-completeness for a variety of sliding-block puzzles. Hearn expressed the idea of building computers from the sliding blocks-many of the logic gates could be connected together, and the user could propagate a signal from one gate to the next by sliding intermediate tiles.…”
Section: Underactuated Controlmentioning
confidence: 99%
“…Many variations of block-pushing puzzles have been explored from a computational complexity viewpoint with a seminal paper proving NP-hardness by Gordon Wilfong in 1991 [64]. The general case of motion-planning when each command moves particles a single unit in a world composed of even a single robot and both fixed and moveable squares is in the complexity class pspace-complete [18,20,38].…”
Section: Manipulationmentioning
confidence: 99%
“…The Find and Verify Solution level solves the puzzle starting from the setup generated in the previous level and using one of the many game solving techniques to evolve from setup to the solution state; for reviews of these techniques we refer to [22][23][24]. Depending on the amenability of the puzzle to different solving strategies, this level may employ algorithms from brute force search to genetic algorithms, game-tree search, and SAT-solving.…”
Section: Workflow Structurementioning
confidence: 99%
“…Following the success of Sudoku, generalizations such as Mojidoku which uses letters instead of digits, and other similar logic puzzles like Hitori, Masyu, Futoshiki, Hashiwokakero, or Nurikabe were developed. Many of them have been proved to be NP-complete [12,5].Interactive ZKPs were introduced by Goldwasser et al [8], and it was then shown that for any NP-complete problem there exists an interactive ZKP protocol [7]. An extension by Ben-Or et al [1] showed that every provable statement can be proved in zero-knowledge.…”
mentioning
confidence: 99%
“…Following the success of Sudoku, generalizations such as Mojidoku which uses letters instead of digits, and other similar logic puzzles like Hitori, Masyu, Futoshiki, Hashiwokakero, or Nurikabe were developed. Many of them have been proved to be NP-complete [12,5].…”
mentioning
confidence: 99%